Viabilidade econômica do cultivo de cacaueiro e bananeira irrigados no Maranhão - Marques, Tiago Malachias (2015)
This work had the purpose of studying the economic feasibility of production of intercropping cacao with banana at ‘São Bernardo’ irrigation district, located at ‘Magalhães de Almeida’ and ‘Araioses’ counties, State of Maranhão (MA). It verifies the opportunity of production business of cacao and banana at Parnaíba river region. The study uses cash flow projections and discounts to Net Present Value (NPV) to assess the economic viability of production business of cocoa and banana in this region of Brazil. Literature searches were performed to analyze soil and climatic characteristics of the micro-region, the physiological characteristics of cacao and its consortium with banana for temporary shading needed during the growth phase of cacao. A high-tech package for cacao production has been suggested, given the need for irrigation for its cultivation. Different productivities and prices of cocoa and banana were used to analyze the economic sensitivity of this business. When designing a cash flow, it was possible to do analysis on the business, feasibility and risks. It should be noted that there are no major producing areas of cacao in the ‘Parnaíba’ river region. However, there are small areas of cacao in semi-arid regions (or savannas). Thus, there is no proof of production on a large scale in order to demonstrate in practical ways some of the economic and financial assumptions used to analyze the feasibility of production of cacao and banana in the ‘São Bernardo’ irrigation district.